The "chain" management of ship-generated waste and cargo residues in the port of Thessaloniki - Palantzas, G.; Naniopoulos, Aristotelis; Theodossiou, Panayiotis (My University, 2005)
According to the Directive 2000/59/EC all European ports should prepare a "plan", describing the management process applied for the reception of ships' generated waste and cargo residues. The "plan" should comply with the modern scientific requirements of environmental protection, taking also into account the existing legislative framework and the international competitive environment, thus requiring a systematic approach where many parameters must be considered. This paper describes the methodological approach applied in the port of Thessaloniki, resulting to a sustainable "plan" and in addition its implementation process, after the appointment of a contractor for the ships' waste management. The management process described reveals the involvement of the various organizations and authorities, outlines the environmental legislative framework that should be applied to all Greek ports and identifies challenges for further improvement
Keywords: Environmental engineering; Harbors; Refuse and refuse disposal; Cargo handling; Environmental protection; Ships; Thessalonikē (Greece)